Frequency of Placenta Previa in Multigravida at Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2018)
Background: Placenta previa is a localization of placenta in the lower uterine segment, near or over the internal os. Multigravida is one of the risk factors of placenta previa. The aim of study is to look for current frequency of placenta previa in multigravida, so that further improvement in diagnosis and treatment modalities can be made in order to decrease the morbidity & mortality related to it in this group.Objective: To determine the frequency of various grades of placenta previa in multigravida at a tertiary care center.Methodology: This is a cross sectional study conducted from December 2014 to June 2015 at the department of Gynecology and Obstetrics, Rajshahi Medical College Hospital. A total of 208 patients enrolled in the study with non -probability purposive sampling technique. All pregnant women with singleton pregnancy of 25-35 years of age in their second or more pregnancy with gestational age ≥ 34 weeks were included. Exclusion criteria observed for patients with multifetal pregnancy, previous history of cesarean section, dilatation and curettage, cervical cone biopsy, myomectomy or any pelvic surgery. All pregnant women had trans-abdominal ultrasound. The presence or absence of placenta previa was reported by an experienced sonologist. The data was analyzed using SPSS version 12.Results: Among the total recruited patients, mean age of these multigravidas was 30.1±5.6 years. The mean parity of our population was 4.02±1.2. The gestational age noted was 38±1.4 weeks as mean.. The frequency of placenta previa was 13 (6.3%) and type IV was the most common type.Conclusion: It is concluded from this study that the frequency of placenta previa in patients of multigravida was 6.3% and apart from other risk factors, multigravidity is an independent risk factor for placenta previa.TAJ 2012; 25: 59-63